Implementasi Proyek Penguatan Profil Pelajar Pancasila Rahmatan Lil'alaamin Di Madrasah Tsanawiyah Sekota Pontianak - Nurhadianto; Mauludea, Hana; Lestari, Jenni (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This research investigates the planning, execution, and evaluation of the Rahmatan lil Alamin Pancasila Student Profile Strengthening Project (P5RA) in several Madrasah Tsanawiyah in Pontianak City, specifically MTs Walisongo, MTs Almadani, and MTs Negeri 1 Pontianak. Adopting a descriptive qualitative method, data were gathered through observations, interviews, and document analysis. The findings reveal that the P5RA initiative was developed in a structured manner, beginning with the establishment of a facilitator team, followed by program socialization and teacher capacity-building sessions. A variety of project-based activities, including student exhibitions, social service programs, and interfaith visits, served as platforms to cultivate core values such as collaboration, tolerance, and social justice. Teachers played a key role as facilitators, guiding students who were actively engaged in the learning process. The program significantly contributed to the development of students' character, particularly in enhancing their empathy, teamwork, and openness to diversity. Despite these positive outcomes, the study also identified several ongoing obstacles. These include time constraints, inconsistent teacher comprehension of the project’s goals, and insufficient involvement from parents. To overcome these challenges, the study recommends ongoing teacher training and strengthening partnerships among educational institutions, families, and community stakeholders. These efforts are crucial to ensure the sustainability and effectiveness of the P5RA in nurturing well-rounded students aligned with the values of Pancasila